Interaction of construction costs and output in Latvia - Danusevics, Martins (University of Latvia, 2020)
Growth of an economy is strongly linked with the growth of the construction sector. An increased construction output must influence the costs in this area. Analysis of the construction output and construction costs in Latvia for the time period since 2006 until 2017 shows an average effect. The main goal is to forecast construction costs and output in Latvia. Comparative analysis of costs and output dynamics was done, and a general trend can be proven, but heteroscedasticity is being observed. The effect of construction output on costs is limited in scale, but similar in general tendency and author offers his discussion for possible reasons for inconsistencies in construction sector changes.
Keywords: construction costs; construction output; salaries; building material costs; Research Subject Categories::SOCIAL SCIENCES::Business and economics